A case study of heat recovery: a heat pump in an industrial site - Abaubakry M'Baye (Renewable Energy and Sustainable Development, 2022)
Greenhouse gases cause global warming of the earth. Carbon dioxide is one of those gases. There are different sources of carbon emission such as industrial activities and deforestation. The application of energy efficiency in industrial environment is one lever to reduce carbon emissions. "Waste" heat represents a significant energy saving potential for industrial companies. Thanks to recovery technologies, waste heat resulting from a process that is not used by it can be recovered for other uses within the same plant or outside. In addition to the economic interest, the recovery of fatal heat is very virtuous from an ecological point of view if the recovered energy avoids the consumption of fossil fuel. It thus improves the carbon footprint of an industrial installation. This article is a case study in an industrial pharmaceutical site in France and explains how a heat pump has been implemented. All the steps of the methodology are detailed: deep analysis of waste heat from the site, calculation and measurement of the reuse potential and research of the most suitable technology to carry out this recovery. This study has permits to reduce by 1/3 site’s carbon emissions. Received: 25 April 2022 Accepted: 14 May 2022 Published: 10 June 2022